2013 World Haptics Conference (WHC) 2013
DOI: 10.1109/whc.2013.6548475
|View full text |Cite
|
Sign up to set email alerts
|

Mass and density estimates contribute to perceived heaviness with weights that depend on the densities' reliability

Abstract: People perceive a smaller and denser object to be heavier than a larger, less dense object of the same mass. We developed a new model of heaviness perception that can explain this size-weight illusion. Modeling followed recent insights on principles of information integration. Perceived heaviness is modeled as a weighted average of one heaviness estimate derived from object mass and another one derived from object density with weights that follow estimate reliabilities. In an experiment, participants judged th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…We found that density estimates depended both on density and mass. This is similar to previous studies that found that heaviness estimates depended on these two object properties as well [3,13] and the finding that participants had more difficulties reporting a difference in heaviness with objects of different compared to equal densities [9]. Hence, density and heaviness perception might be closely related.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that density estimates depended both on density and mass. This is similar to previous studies that found that heaviness estimates depended on these two object properties as well [3,13] and the finding that participants had more difficulties reporting a difference in heaviness with objects of different compared to equal densities [9]. Hence, density and heaviness perception might be closely related.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, accuracy declines when the factors change in opposite directions [9]. More recently, it was proposed that heaviness estimation is formed from a weighted combination of mass and density information, depending on the properties' reliability [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bottom-up explanations reject the idea of illusions as a failure of the perceptual system, reclassifying the illusory weight difference as the detection of some other action-relevant variable that varies between the stimuli. Candidate variables include the detection of difference in an object's density (Drewing & Tiest, 2013;Grandy & Westwood, 2006), inertia tensor (Amazeen & Turvey, 1996), or some reflection of our perceptual expertise in detecting an object's "throwability"-the relationship between volume and mass, which allows some items to be thrown further than others- (Zhu & Bingham, 2011). By contrast, the top-down explanation is conceptually similar to that put forward for the MWI and golf ball illusion, with cognitive (rather than sensorimotor) expectations interacting with sensory information from the hands and arms to drive the illusion that the objects have different weights from one another.…”
mentioning
confidence: 99%